Alterations in Phospholipid Catabolism in Mycobacterium Tuberculosis LysX Mutant - Maloney, Erin A.; Lun, Shichun; Stankowska, Dorota; Guo, Haidan; RAJAGOPALAN, MALINI; Bishai, William; Madiraju, Murty V. (Frontiers in Microbiology, 2011)
Mycobacterium tuberculosis lysX mutant, defective for production of lysinylated phosphatidylglycerol (L-PG), is sensitive to cationic antimicrobial peptides, is not proficient for proliferation in mice lungs and exhibits altered membrane potential [1]. In the present study we show that a lysX complement strain expressing lysX from inducible tet promoter is proficient in restoring lysX phenotypes confirming that the observed phenotypes are specific to lysX. To evaluate the correlation between changes in membrane potential and lysX activity, we visualized regions of cardiolipin (CL), one of the abundant phospholipids of mycobacteria, by staining with fluorescent dye 10-N-nonyl-acridine orange (NAO) and found that CL is localized as bright spots at septal regions and poles of actively dividing cells, but not in stationary phase cells. lysX mutants were elongated and showed more numerous and brighter CL staining at both midcell and quarter cell septa, compared with wild type, indicating a defect in the cell division process. Evaluation of 14C-acetic acid incorporation into major phospholipids such as CL, phosphatidylethanolamine (PE), phosphatidylinositol and their degradation between lysX mutant and its parent revealed differences in the turnover of PE and PI. Our results favor a hypothesis that alterations in phospholipid metabolism could be contributing to changes in membrane potential, hence the observed phenotype of lysX mutant.